The Effect of AI-Assisted Marketing on MSME Product Promotion Effectiveness: The Role of Customer Engagement among MSMEs in Dalu Sepuluh B Village - Sri Wahyuni; Zulham; Buyung Solihin Hasugian (Information Technology Education Journal, 2026)
Purpose –Examine the effect of AI-Assisted Marketing on Promotional Effectiveness and analyze Customer Engagement as a mediating variable among MSMEs in Dalu Sepuluh B Village. The study addresses the limited use of AI to improve promotional effectiveness and customer engagement, particularly among rural MSMEs. Design/methods/approach –Employs a quantitative explanatory cross-sectional design to examine the effect of AI-Assisted Marketing on Promotional Effectiveness. The study involves 100 MSME respondents selected through purposive sampling. Data are collected using a questionnaire consisting of 12 indicators measured on a five-point Likert scale. Data analysis is conducted using PLS-SEM through SmartPLS, including assessment of outer loadings, Cronbach's Alpha, Composite Reliability, AVE, HTMT, path coefficients, t-statistics, p-values, R², and f². Findings – H1 supported: AI-Assisted Marketing has a positive and significant effect on β = 0.509; p < 0.001, H2 supported: β = 0.394; p < 0.001, H3 supported: AI-Assisted Marketing has a direct and significant effect on Promotional Effectiveness (β = 0.281; p = 0.004), H4 supported: Customer Engagement significantly mediates indirect effect = 0.201, The R² for Customer Engagement = 0.259, The R² for Promotional Effectiveness = 0.347. Research implications/limitations –that AI can improve promotional effectiveness and customer engagement. However, generalizability is limited to the context of MSMEs in Dalu Sepuluh B Village. The cross-sectional design and self-reported data also limit causal interpretation. Originality/value – the mechanism linking AI-Assisted Marketing, Customer Engagement, and Promotional Effectiveness, rather than focusing solely on AI adoption. It contributes to the literature on AI-enabled marketing and MSME digital transformation.